Magnetic field and orbit of the star β CrB. Issue 2 (21st June 2018) - Han, Inwoo; Valyavin, G; Galazutdinov, G; Plachinda, S; Butkovskaya, V; Lee, B C; Kim, Kang-Min; Jeong, Gwanghui; Romanyuk, I; Burlakova, T
ABSTRACT: We present the results of long term high-resolution spectral and spectro-polarimetric observations of the classic spectroscopic binary star β Coronae Borealis, which is also well known for its chemical peculiarity and strong magnetic field. One of the main objectives of these observations was to check some suggestions of the presence of a third low-mass component in the system. Analysing our own radial velocity (RV) measurements of β Coronae Borealis obtained between 2004 and 2013 together with other RV and astrometric data taken from the literature, we have considerably improved the orbital elements of the star. Using residual RVs obtained after subtracting the orbit from the observed RV, we detected a significant periodic signal consistent with the well-known 18.4868-d rotation/magnetic period of the star. The shape of the residual RVs folded with the rotation period exhibits a bimodal structure. In order to clarify the origin of the residual RV variation, we model the RV variation due to rotational modulation Zeeman patterns in the spectral lines of β Coronae Borealis spectra. The results of this analysis and the investigation of chemical inhomogeneities in the spectra of β Coronae Borealis convincingly support the 'magnetic' nature of the observed RV variations.